Rational development of transformation in Clostridium thermocellum ATCC 27405 via complete methylome analysis and evasion of native restriction–modification systems. (1st October 2019) - Riley, Lauren A; Ji, Lexiang; Schmitz, Robert J; Westpheling, Janet; Guss, Adam M
Abstract: A major barrier to both metabolic engineering and fundamental biological studies is the lack of genetic tools in most microorganisms. One example is Clostridium thermocellum ATCC 27405 T, where genetic tools are not available to help validate decades of hypotheses. A significant barrier to DNA transformation is restriction–modification systems, which defend against foreign DNA methylated differently than the host. To determine the active restriction–modification systems in this strain, we performed complete methylome analysis via single-molecule, real-time sequencing to detect 6-methyladenine and 4-methylcytosine and the rarely used whole-genome bisulfite sequencing to detect 5-methylcytosine. Multiple active systems were identified, and corresponding DNA methyltransferases were expressed from the Escherichia coli chromosome to mimic the C. thermocellum methylome. Plasmid methylation was experimentally validated and successfully electroporated into C. thermocellum ATCC 27405. This combined approach enabled genetic modification of the C. thermocellum -type strain and acts as a blueprint for transformation of other non-model microorganisms.